Teamwork in clinical genomics: A dynamic sociotechnical healthcare setting. Issue 6 (5th May 2021) - Best, Stephanie; Brown, Helen; Stark, Zornitza; Long, Janet C.; Ng, Larissa; Braithwaite, Jeffrey; Taylor, Natalie
Abstract: Rationale, aims and objectives: Teamworking across sociotechnical boundaries in healthcare is growing as technological advances in medicine abound. With this progress, teams need to find new ways of working together in non‐traditional settings. The novel field of clinical genomics provides the opportunity to rethink the existing approach to teamworking and how it needs to evolve. Our aim was to identify the key factors influencing teamworking in the emerging field of clinical genomics and how can they be applied in practice. Method: We drew on three qualitative datasets from interviews undertaken in Australia, 2018/2019, that explored determinants of implementation of clinical genomics with laboratory scientists ( n  = 7), service and programme leads ( n  = 21), project officers ( n  = 2), clinical genetics staff ( n  = 26) and other medical specialists ( n  = 21). Data were analysed using a theory‐informed matrix approach to identify themes related to teamworking. Results: We identify that teams in clinical genomics work in an elongated adaptive context where there is rapid evolution of the knowledge base, shifting expectations of staff roles, and fast changes of technology. Delivering care in this setting brings additional challenges to teamworking as members strive to stay abreast of current knowledge and technology. We identify four themes: (a) the role of the team in keeping knowledge up‐to‐date; (b) professional identity; (c) team adaptability, and (d) practical/organisational considerations. Conclusion: Challenges to teamworking that arise in the elongated adaptive context do not always fit traditional ways of working, and innovative strategies will need to be adopted to ensure the diagnostic advances of clinical genomics are realised. Provision of time and permission for team members to share knowledge and evolve, promoting capacity building, nurturing trustful relationships and establishing boundaries are amongst the practice recommendations for organisational and team leaders, even though these activities may disrupt existing ways of working or hierarchical structures.